KEPEMILIKAN INSTITUSI, PILIHAN STRATEGIS, DAN EFISIENSI PERUSAHAAN GO PUBLIC DI INDONESIA - Marsella Isani Edoway (Jurnal Riset Akuntansi dan Keuangan, 2016)
; "> Based on the tenets of capital allocation systems theory, stewardship theory, and ‘going concern’concept of business, institutional ownership is proposed to affect corporate Efficiency, both directly andindirectly, in large Indonesian corporations through a set of three firm-level choices: product/marketdevelopment, capital intensity, and leverage. Using data on 59 corporations drawn from all industrysectors in Indonesian, and applying a partial mediation technique, this study tests an integrated, causalmodel of the relationships among these variables. Results show mixed support for the model. No directrelationship between institutional ownership and Efficiency is observed. However, institutionalownership affects Efficiency indirectly through product/market development and capital intensity.Although almost variable has mediation affect between institutional ownership and Efficiency,nevertheless institutional ownership has no significant relationship with leverege which also has nosignificant relationship with Efici.Keyword: institutional ownership, product/market development, capital intensity, leverage, efficiency